The right to be forgotten in the light of the consent of the data subject. Issue 2 (April 2016) - Bartolini, Cesare; Siry, Lawrence
Abstract: Recently, the Court of Justice of the European Union issued decision C-131/12, which was considered a major breakthrough in Internet data protection. The general public welcomed this decision as an actualization of the controversial "right to be forgotten", which was introduced in the initial draft for a new regulation on data protection and repeatedly amended, due to objections by various Member States and major companies involved in massive processing of personal data. This paper attempts to delve into the content of that decision and examine if it indeed involves the right to be forgotten, if such a right exists at all, and to what extent it can be stated and enforced.